Effectiveness of Electroacupuncture on Body Mass Index and Waist Circumference in Overweight Cases at Campus 1 of the Health Polytechnic of the Ministry Of Health in Surakarta - Bilistolen, Nanda Wira Febriyanti; Patriyani, Ros Endah Happy; Mutiah, Nurmila (Indonesian Journal of Acupuncture, 2024)
Excess weight is the root of various non- communicable diseases that are still a health problem in Indonesia. Acupuncture can reduce weight by stimulating the satiety center in the hypothalamus and suppressing the hunger center. This study aims to determine the effectiveness of electroacupuncture therapy (Body Acupuncture and Ear Acupuncture) and electroacupuncture therapy (body acupuncture) on body mass index and waist circumference in cases of excess weight at Campus 1 of the Health Polytechnic of the Ministry of Health, Surakarta. This study used a Quasi-Experimental research design with a two-group pre-test-post-test design and a purposive sampling technique with a sample size of 42 subjects. The group consisted of 21 subjects for group 1 and 21 subjects for group 2. The results of the Wilcoxon test for electroacupuncture therapy (body acupuncture and ear acupuncture) with ρ<0.001, and for electroacupuncture therapy (body acupuncture) with ρ<0.001. It can be concluded that electroacupuncture therapy (body acupuncture and ear acupuncture) and electroacupuncture therapy (body acupuncture) significantly affect body mass index and waist circumference in cases of overweight. Conclusion Electroacupuncture therapy (Body Acupuncture and Ear Acupuncture) is effective in changing body mass index and waist circumference at Campus 1 of the Ministry of Health Polytechnic of Surakarta